Liquidity Risk, Interconnectedness, and Investor Behavior in Investment Funds - Szabo, Milan (2024)
Funds' liquidity transformation is inevitable, yet it fundamentally contributes to systemic vulnerabilities arising from open-ended fund activities. The dissertation studies the factors amplifying liquidity risks in open-ended funds stemming from their structural liquidity mismatches. I study how these mismatches influence investors' and managers' behaviors. The dissertation also examines increasing interconnectedness due to cross-fund exposures and shows this may be related to the mismatch. The dissertation is a collection of four essays, each studying Czech open-end funds. The first essay explores inflows and outflows patterns in retail equity funds related to past and future performance. I find that retail investors become sensitive to bad performance in times of aggregate illiquidity and while investing in funds that hold more illiquid assets. Moreover, I document that when facing illiquidity and deteriorating performance, under-performing equity funds experience lower investor purchases and a larger share of redemption requests. I observe similar investor behaviour in periods when retail investors face constraints on their disposable income. The second essay explores liquidity management practices in bond and equity funds. I reconstruct funds’ cash flows to study liquidity transformation and liquidity management in investment funds. I study how portfolio illiquidity and current market conditions influence the joint behavior between investor redemptions and funds’ liquidity management. The third essay explores increasing funds’ investing in other funds. I study the implications of the growing interconnectedness. I show that cross-fund holdings boosted diversification and returns, albeit with increased volatility. I show that funds primarily sold fund shares compared to other assets to meet large redemptions and that funds increase sales of held funds experiencing investor outflows.